A low‐profile high‐gain multi‐beam antenna based on 3D‐printed cylindrical Luneburg lens. Issue 7 (13th April 2021) - Cao, Yuanxi; Yan, Sen
Abstract: In this article, a low‐profile and high‐gain multi‐beam antenna is proposed. The antenna consists of a cylindrical Luneburg lens based planar beamforming network, a folded double‐layer guided‐wave structure, and a leaky wave antenna (LWA) array. All the three parts are manufactured by 3D printing technology. The lens is realized by an n‐shaped gradual thickness unit to realize the refractive index variation of Luneburg lens in a parallel plate waveguide. The lens and the LWA array are folded into a double‐layer guided wave structure, which transforms the planar wave from the flat Luneburg lens to the LWA array to realize the antenna miniaturization. The antenna is excited by a radially placed microstrip antenna array at the focal plane of the lens. The proposed antenna has seven beams with minimum −2.5 dB crossover level, and the scanning range is ±29°. The broadside gain is 19.8 dB, and the gain variation in scan range is 2.7 dB. The proposed antenna is fabricated and tested, and the measured results agree well with the simulated ones. Due to the advantages including low‐profile, high aperture efficiency, high radiation efficiency, and low cost, the proposed design can find its applications in multi‐beam radar and communication systems.